The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/foods11040580
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Eruca sativa Defatted Seed Meal on Visceral Pain and Intestinal Damage Resulting from Colitis in Rats

Abstract: Most therapies used in patients affected by inflammatory bowel diseases are ineffective in preventing the development of chronic visceral hypersensitivity, mainly due to inflammation-induced enteric neuroplasticity. Glucosinolates, secondary metabolites mainly of Brassicaceae with anti-inflammatory and neuroprotective properties, are effective in treating both neuropathic and arthritis pain through H2S release and Kv7 potassium channel activation. The aim of this work was to investigate the protective and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…In this context, Brassicaceae plants emerged to be ideal candidates, since the ITCs contained in these plants can modulate both inflammatory response and oxidative stress [ 9 , 10 ]; they also display potential benefits for the gut microbiota [ 12 , 13 , 14 , 56 ], which has high relevance in gut pain associated with colitis [ 17 , 57 , 58 ]. Several studies in the literature attest that ITCs are effective against both inflammatory and neuropathic pain by the slow release of H 2 S in vivo , and by the positive modulation of Kv7 potassium channels activity [ 18 , 20 , 21 , 25 , 59 ], which are involved in different physiological processes like the regulation of blood pressure and the transmission of painful stimuli [ 11 , 19 , 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, Brassicaceae plants emerged to be ideal candidates, since the ITCs contained in these plants can modulate both inflammatory response and oxidative stress [ 9 , 10 ]; they also display potential benefits for the gut microbiota [ 12 , 13 , 14 , 56 ], which has high relevance in gut pain associated with colitis [ 17 , 57 , 58 ]. Several studies in the literature attest that ITCs are effective against both inflammatory and neuropathic pain by the slow release of H 2 S in vivo , and by the positive modulation of Kv7 potassium channels activity [ 18 , 20 , 21 , 25 , 59 ], which are involved in different physiological processes like the regulation of blood pressure and the transmission of painful stimuli [ 11 , 19 , 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compounds were acutely administered as follows. The doses of Camelina sativa DSM (0.1–1 g kg −1 po) were chosen based on previous evidence [ 25 ]. Camelina sativa DSM was bioactivated by adding 30 μL mL −1 of myrosinase (32 U mL −1 ) 15 min before the administration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at H&E-stained colon slices (Figure 2D and Figure S1), it was observed that after the interventive treatment with ALCAR, the submucosa of DNBS animals was significantly less thick in comparison to that of DNBS + vehicle animals (black double arrows), the mucosa was almost restored, and the inflammatory infiltrate was restricted to the submucosa (white arrows). An increased mast cell and eosinophil infiltration within the colon is one of the peripheral mechanisms that has been associated with visceral sensitivity persistence [3,32], and it is usually reduced by treatment that prevents pain establishment by protecting the colon from the inflammatory insult [30,33,34]. Regarding the effect of ALCAR, neither the preventive nor the interventive protocol had any effect on mast cell and eosinophil infiltration in the submucosae of DNBS-treated animals (Figure 2E,F), as clearly emerges in the representative picture, showing mast cell granules stained in purple and eosinophils stained in pink with GIEMSA (Figure 2G and Figure S2).…”
Section: Effect Of Alcar On Colon Damage and Mast Cell/eosinophils In...mentioning
confidence: 99%
“…The same research group demonstrated that the water extract of Brassicaceae plant Eruca sativa Mill, displays visceral anti-nociceptive effect in a DNBS- rat model. This effect, attributable to the high glucosinolate content, was suggested to be due to the release of hydrogen sulphide (H 2 S) and the positive modulation of Kv 7 potassium channel activity [ 95 ]. The Brassicaceae Maca ( Lepidium meyenii ) is the only source of Macamides, a class of bioactive amide alkaloids.…”
Section: Brassicaceae and Inflammation: Evidence Of Anti-inflammatory...mentioning
confidence: 99%